Religious Moderation as a Framework for Peaceful Coexistence in Contemporary Islamic Thought - Pahrudin, Ade; Fachiroh, Wirdah; Sahabuddin, Sahabuddin; Shafira, Elsa Balqis; Rinaldo, Ahmad Rizky; Najwa, Samarra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Amidst growing religious polarization and ideological rigidity, the call for moderation in Islam emerges as a theological and moral necessity. This study examines the concept of religious moderation (wasatiyyah) in contemporary Islamic thought, considering it across diverse intellectual traditions and sociocultural contexts. This paper employs a library research approach combined with a descriptive-analytical method. It draws from the works and discourses of eleven scholars: Quraish Shihab, Yusuf al-Qaradawi, Muchlis Hanafi, Dainawi, Husain Thabathabai, and Abdurrahman Wahid, Musthofa Bisri, Joachim Wach, Djamaluddin Ahmad, and Afifuddin Muhajir. These scholars' ideas on religious moderation are documented in scholarly articles widely circulated on the Moraref portal and in academic journals affiliated with Islamic higher education institutions (PTKIN). The analysis thematically explores ethical principles such as tolerance, balance, justice, humility, and human dignity. Rather than treating moderation as a passive middle ground, these scholars frame it as an active, intentional ethical-spiritual orientation rooted in Islamic epistemology and responsiveness to plural realities. The findings demonstrate that, as articulated by these contemporary Islamic thought, religious moderation presents a spiritually grounded, intellectually engaged, and socially adaptive framework for constructing peace through transformative education, inclusive dialogue, and inner moral reform in an increasingly fragmented and globalized world.